Metabolite and gut microbiota co-biomarkers in Danggui Shaoyao San: insights into a shared therapeutic approach - Fu, Xin; Peng, Dinghan; Yu, Yang; Cao, Mingguo; Zheng, Xin; Wu, Songquan (Frontiers in Pharmacology, 2026)
Danggui Shaoyao San (DSS), a classical multi-herbal formulation of traditional Chinese medicine, demonstrates therapeutic potential for Type 2 Diabetes Mellitus (T2DM), Alzheimer’s Disease (AD), and Polycystic Ovary Syndrome (PCOS). This review proposes a unified mechanism whereby DSS exerts its effects by modulating a network of shared pathological biomarkers across these disorders. We identify tryptophan (Trp) and phenylalanine (Phe) as host-derived metabolic biomarkers in plasma, and the gut bacterial phylum Bacteroidetes as a shared gut microbial biomarker. The therapeutic actions of DSS are mediated by its botanical constituents (e.g., ligustilides, paeoniflorin, ferulic acid), which help correct the dysregulated Trp-kynurenine and Phe metabolic pathways, while simultaneously enriching Bacteroidetes to alleviate gut dysbiosis and rebalance the gut-brain axis. This coordinated regulation of shared host metabolic and gut microbial biomarkers provides a scientific rationale for applying DSS as a multi-targeted agent, illustrating a molecular basis for a shared therapeutic approach.